The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/cji.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Impact of Anti-TNFα Treatment of Severe Immune Checkpoint Inhibitor-induced Colitis in Advanced Melanoma: The Mecolit Survey

Abstract: Immune checkpoint inhibitors (ICI) significantly improve overall survival (OS) in patients with advanced melanoma, but immune-related colitis may occur and warrant anti-tumor necrosis factor α (TNFα) treatment in severe forms. A nationwide, multicenter retrospective survey was conducted to assess both, the real-life incidence of grade 3/4 ICI-induced colitis treated with anti-TNFα, in patients with advanced melanoma, and the consequence of this therapeutic strategy on disease outcome. All patients with advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 30 publications
1
55
1
Order By: Relevance
“…The impact anti-TNF antibodies have on anti-cancer immune responses in these settings are not known. A recent study indicates that 1% of patients with advanced melanoma treated by ICI develop severe colitis, which can be efficiently cured with one infliximab infusion in most of the patients, without affecting disease outcome (32). A clinical study evaluating the tolerability of infliximab in advanced cancer patients shows no dose-limiting toxic (DLT) effects and no evidence of disease acceleration in any patient.…”
Section: Combining Tnf Blockade To Immune Checkpoint Blockers To Treamentioning
confidence: 99%
“…The impact anti-TNF antibodies have on anti-cancer immune responses in these settings are not known. A recent study indicates that 1% of patients with advanced melanoma treated by ICI develop severe colitis, which can be efficiently cured with one infliximab infusion in most of the patients, without affecting disease outcome (32). A clinical study evaluating the tolerability of infliximab in advanced cancer patients shows no dose-limiting toxic (DLT) effects and no evidence of disease acceleration in any patient.…”
Section: Combining Tnf Blockade To Immune Checkpoint Blockers To Treamentioning
confidence: 99%
“…The irAEs, i.g. colitis, are managed by corticosteroid administration (270,271), but refractory cases are treated with infliximab once ICB is suspended. Considering the aforementioned mechanisms of TNFα-induced ICB resistance, preclinical studies investigated the prophylactic effect of TNFα blockade both to impede irAEs development and to enhance ICB's efficacy.…”
Section: Immune Check-point Inhibitorsmentioning
confidence: 99%
“…infliximab treated patients experienced a response, 42 Six studies reported safety outcomes in the context of infliximab 10,25,[36][37][38]40 across 171 infliximab-treated patients. Of 36 infliximab-treated corticosteroid refractory patients, Harding et al describe hypersensitivity reactions in two and a fungal pneumonia in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Where dose of infliximab used was defined, it was 5 mg/ kg. 9,13,14,16,[38][39][40] The number of infliximab doses administered was reported in 14 studies, 9,10,13,14,16,25,32,[35][36][37][38][39][40][41] with three of these not included in the quantitative analysis as too few patients were treated.…”
Section: Efficacy Of Infliximabmentioning
confidence: 99%